Tremont Street, April 1900 - Unknown (Tufts Archival Research Center, 2005)
Street-level view of a horse-drawn wagon moving down Tremont Street. The Massachusetts State House, located on Beacon Street, is included in the background of the photograph. Pedestrians are visible near the subway entrance at Boston Common, which is located along the right side of the photograph. Snow blankets Tremont Street and Boston Common. 3 15/16 x 4 7/8, 4 1/16 x 5 overall Photographs